The Effects of Design-Thinking-Based AI Education Programs Utilizing Generative AI on Korean Middle School Students’ Creative Problem-Solving Ability - Kim, Seong-Won; Lim, Suhun; Hong, Seung-Ju; Lee, Youngjun (Society of Visual Informatics, 2025)
With the rise of digital transformation, fostering AI talent has become essential. Design thinking is gaining attention in AI education for enhancing creative problem-solving and facilitating a structured approach to problem-solving. A key stage in design thinking is Empathize, which involves a deep understanding of the problem. However, educational constraints often limit meaningful empathy activities. To address this, this study developed a design-thinking-based AI education program incorporating generative AI and evaluated its effectiveness. A total of 117 second-year middle school students in South Korea participated (57 in the experimental group, 60 in the control group). The experimental group used generative AI in the Empathize stage to create personas and storytelling activities, while the control group completed the stage without AI. The program’s impact was assessed by measuring changes in creative problem-solving skills and AI literacy. Results showed significant improvement in AI literacy for both groups, confirming the program’s effectiveness in developing AI literacy. However, creative problem-solving skills improved only in the experimental group, suggesting that generative AI enhances contextual understanding and emotional engagement, which in turn leads to better problem definition and idea generation. These findings highlight the potential of generative AI in AI education, particularly in facilitating deeper empathy and structured problem-solving. Future research should explore its application across different educational levels to validate its pedagogical impact further.